Grey-Box Modeling Method for Single Degree of Freedom Nonlinear Vibration Isolation System - Wang, Zhi-Ao; Luo, Zhong; Zhu, Yun-Peng; Zhou, Guang-Ze; Yu, Bing (Journal of Vibration Testing and System Dynamics, 2026)
The present study aims to investigate a new modeling method of single degree of freedom nonlinear vibration isolation system. Grey-box theory is used to model the system. Grey-box model is a combination of white-box model and black-box model. The white-box model is a simple component of vibration isolation system expressed by the differential models. In contrast to the white-box model, the black-box model is a NARX (Nonlinear AutoregRessive with eXogenous input) model, which is used to represent the complex structural components in the vibration isolation system that cannot be built with differential model. Based on the interface analysis, the grey-box model of vibration isolation system is obtained by integrating the white box model and the black box model. Compared with traditional physical modeling and finite element simulation, the method proposed in this paper is more rapid and cost saving. In addition, the grey-box modeling method can also be applied to the design of vibration isolators. Finally, a single degree of freedom nonlinear vibration isolation system is taken as an example to verify the correctness of the proposed method. The results of the study indicate that the proposed method is effective.